Synergized Academic with Student Activities (SAA): learning through community engagement - Abd Karim, Nur Qurratul Nusrah; Mohd Fauzie, Nur Siti Khadeejah; Karim, Fatimah (Islam on Web, 2025)
Education at University Islam Antarabangsa Malaysia (IIUM) has always been rooted in the belief that knowledge should not remain confined within classrooms, lecture notes, or examinations. Instead, learning is meant to shape character, nurture responsibility, and prepare students to contribute meaningfully to society. In line with this philosophy, the Synergized Academic with Student Activities (SAA) initiative serves as a platform that bridges academic learning with real-life engagement.